2022
DOI: 10.1029/2021jd036289
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flux Measurements of the Near‐Surface and Residual‐Layer Small Particle Events

Abstract: According to recent field studies, almost half of the New Particle Formation (NPF) events occur aloft, in a residual layer, near the top of the boundary layer. Therefore, measurements of the meteorological parameters, precursor gas concentrations, and aerosol loadings conducted at the ground level are often not representative of the conditions where the NPFs take place. This paper presents new measurements obtained during the Turbulent Flux Measurements of the Residual Layer Nucleation Particles, conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Meteorology has been found to be one of the primary determinants of PM variation in the atmosphere (Liu and Cui, 2014;Trivedi et al, 2014). Studies have shown that meteorological parameters such as wind speed, temperature, relative humidity, solar radiation, rainfall, atmospheric boundary layer, pressure system play a significant role in explaining PM variation in the USA, China, and India (Islam et al, 2022a;Singh et al, 2021;Ilias et al, 2020;Wang et al, 2013). Hassan et al (2020) investigated the long-term PM relationship with meteorological parameters in Malaysia and identified that PM is strongly…”
Section: Introductionmentioning
confidence: 99%
“…Meteorology has been found to be one of the primary determinants of PM variation in the atmosphere (Liu and Cui, 2014;Trivedi et al, 2014). Studies have shown that meteorological parameters such as wind speed, temperature, relative humidity, solar radiation, rainfall, atmospheric boundary layer, pressure system play a significant role in explaining PM variation in the USA, China, and India (Islam et al, 2022a;Singh et al, 2021;Ilias et al, 2020;Wang et al, 2013). Hassan et al (2020) investigated the long-term PM relationship with meteorological parameters in Malaysia and identified that PM is strongly…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of explosive growth can result in a sudden augmentation of particles, with significant implications for air quality, climate, and human health. Understanding the underlying mechanisms and factors contributing to this explosive particle growth is vital for the accurate assessment of particle impacts [20]. Furthermore, these newly formed particles can potentially be activated as cloud condensation nuclei (CCN) after hours of growth [21].…”
Section: Introductionmentioning
confidence: 99%